Analysis of Distribution of Contact Loads on Tool Surfaces - Urinov Nasillo Fayzilloevich; Juraev Jurabek Malikovich; Odinaev Rustam Sobirovich (International Journal on Human-Computing Studies, 2021)
The article covers an analysis of magnitude and nature of distribution of contact loads on tool surfaces in order to evaluate the strength of the tool, as well as the modeling of the cutting tool.